Influence of abutment transmucosal height on biomechanical behavior in narrow platform implants - Almeida Júnior, Jenival Correa de; Machado, Marco Teixeira; Lemos, Ygor Carlo de Aguiar; Neto, Ervino Siebel (International Journal of Advanced Engineering Research and Science, 2021)
The distribution and transfer of masticatory loads through prosthetic components, implants and peri-implant bone is a critical issue that can influence the rehabilitation treatment and result in its failure. Thus, this in silico study aimed to evaluate the influence of the transmucosal height of the prosthetic abutment and the diameter of the implants on the biomechanical behavior of dental implants. Two virtual models of 10 mm long Morse taper implants were built combining components with transmucosal (height 1.5 and 2.5 mm) in two diameters of platform (2.9 or 3.3 mm). Each set was positioned in a virtual bone model, where a lower central incisor was designed and exported for mathematical analysis. A 0.50 mm mesh was created after 5 % convergence analysis, and a 50 N load was applied to the incisolingual surface of the prosthetic crown at an angle of 30 °. The stress distribution generated by load was analyzed in the prosthetic components according to the von Mises stress criterion and in the cortical and medullary bones by means of shear stress. The use of an abutment with a 2.5 mm transmucosal height resulted in higher stress concentration values (758.86 and 731.63 MPa, 2.9x10 and 3.3x10 mm respectively) regardless of the diameter of the implant used. The increase in the diameter of the platform (3.3 mm) produced a slight reduction in the shear stress in the cortical bone. The medullary bone was not affected by the implant-pillar relationship. It was concluded that implants with a larger platform diameter and a higher transmucosal height decreased the stress concentration in the implant and in the cortical bone.